Problem Malnutrisi pada Orang Tua : Tinjauan Faktor Risiko, Konsekuensi, dan Pendekatan Terapi - Sunarti, Sri; Fatma, Siti; Putri, Fara; Oktavia, Nur; Miamaretta, Alifia; Salsabiila, Syahidah (Jurnal Klinik dan Riset Kesehatan, 2023)
Aging is an unavoidable part of life, which means process of turning into frail person with reduce physiologic functions and increased disease susceptibility through various mechanisms, including age-related changes in lifestyle, disease conditions, sosial and environmental factors that may affect dietary behaviors and nutritional status. Malnutrition are common symptoms in elderly and are related to various factors including eating problem and comorbid diseases. Screening for eating disorder, comorbid diseases, and mental diseases such as depression, and anxiety are essential. Managing malnutrition is important, with comprehensive treatment including lifestyle changes, controlling comorbid disease, and also simple intervensions such as nutritional supplementation or modified diets could improved the health status.